IMPLEMENTASI PROGRAM PENGABDIAN MASYARAKAT TEMATIK POSDAYA BERBASIS MASJID MENUJU KEMANDIRIAN KELUARGA SEJAHTERA - Ahmad Hasyim Fauzan (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2018)
Tridharma Colleges set up college to care about solving problems in society, including through outreach activities. College real work (CCN) Thematic Posdaya based Mosque is a model of public service that focuses on empowerment of the family in the aspect of education, health care, entrepreneurship, and the environment. CCN put students living together the community in shaping the institutions of the community or developing civic institutions mainly existing became Posdaya. Through the vehicle of Posdaya mosque-based student community together identify the problems and moving all the potential that exists for the sake of the progress of the society. Students are able to synergize and mengimplemen-tasikan science practiced with the life of the community, caring, leadership, cooperation, learning the local wisdom, order value, as well as the norms of society. CCN Thematic Posdayaberbasis Mosque is a system that needs preparation, implementation, guidance, mentoring, monitoring and evaluation, and follow-up activities on an ongoing basis to achieve optimal results.